2018
DOI: 10.1097/phm.0000000000000970
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Physiotherapy Interventions on Spasticity in People With Multiple Sclerosis

Abstract: Physiotherapy interventions can be a safe and beneficial option for spasticity in people with multiple sclerosis. No firm conclusion can be drawn on overall spasticity. Further researches in different spasticity aspects are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 83 publications
1
29
0
3
Order By: Relevance
“…Patients undergoing PT intervention combined with nabiximols had higher probability of having a CRR, compared to those treated only with nabiximols. A recent meta-analysis demonstrated that PT interventions are a safe and beneficial option for spasticity in patients with MS [14]. Due to the multicenter nature of our survey, we considered a heterogeneous array of PT programs including all our patients; accordingly, we preferred to divide bimodally the study population in those attending or not attending PT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing PT intervention combined with nabiximols had higher probability of having a CRR, compared to those treated only with nabiximols. A recent meta-analysis demonstrated that PT interventions are a safe and beneficial option for spasticity in patients with MS [14]. Due to the multicenter nature of our survey, we considered a heterogeneous array of PT programs including all our patients; accordingly, we preferred to divide bimodally the study population in those attending or not attending PT.…”
Section: Discussionmentioning
confidence: 99%
“…The PT interventions are intended to maintain the muscle length, prevent contracture, and change mechanical properties of the musculoskeletal system and plasticity within the central nervous system. PT interventions also seem a safe treatment, with adverse events and withdrawals being minor and rare [1415].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, research on the efficacy of physical exercise in treatment of other brain disorders is still in its infancy and therefore not part of the standard care. Although several studies have investigated the effect of physical exercise in different chronic brain disorders such as Alzheimer's disease (AD) [17,18], multiple sclerosis (MS) [19][20][21], Parkinson's disease (PD) [22,23], Schizophrenia (Sz) [24,25] and unipolar depression (UD) [26][27][28], results and mainly recommendations for clinical practice have been highly diverse [29]. As a consequence, current evidence for efficacy of exercise therapy is still disputed and exercise is not part of the regular care offer for patients with aforementioned disorders in most countries.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of systematic reviews for non-pharmacological interventions for spasticity in adults found low quality evidence for rehabilitation programs, including stretching; physical activity programs with stretching, and very low evidence for passive movement [48]. Another review, specifically of physical therapy interventions for spasticity reported the best quality evidence for beneficial effects for exercise therapy, especially robot gait training, and outpatient exercise programs, both requiring supervision or 1:1 treatment, but concluded no firm conclusions can be drawn on the effect of physical therapy interventions on overall spasticity [49].…”
Section: Discussionmentioning
confidence: 99%